BIOSYNTHESIS AND COMPREHENSIVE STRUCTURAL CHARACTERIZATION OF TiO₂-LOADED BENTONITE NANOCOMPOSITES USING ORANGE PEEL EXTRACT - Yahaya, M. K.; Sumaila, Abdulmumuni; Yahaya, R. A.; Abdulsalam, S.; Jimoh, Ibrahim; Abdulkarim, I.; Sumaila, A. O.; Yusuf, R. O. (FUDMA Journal of Sciences, 2025)
This study reports a green biosynthesis route for TiO₂-loaded bentonite nanocomposites (BTNCs) using orange peel extract as a natural reducing and stabilizing agent to integrate the photocatalytic and adsorptive properties of titanium dioxide (TiO₂) and bentonite clay respectively. Characterization of the synthesized nanocomposites was carried out using a suite of analytical techniques, including X-ray diffraction (XRD), scanning electron microscopy (SEM), and Raman spectroscopy. Characterization via XRD, SEM, and Raman spectroscopy confirmed the successful incorporation of anatase TiO₂ nanoparticles ( 17.5 nm) uniformly dispersed within the bentonite matrix, with evidence of Ti–O–Si bond formation indicating strong interaction between TiO₂ and bentonite. The eco-friendly synthesis method discourages the use of toxic reagents and offers multifunctional nanomaterials with promising applications in photocatalytic wastewater treatment.